Strategic Economic Management : ARDL Analysis of Trade, FDI, and Growth in G20 Nations - Kumar, Rajesh; Neogi, Debasis (Prabandhan: Indian Journal of Management, 2025)
Purpose : This study examined how trade openness interacted with foreign direct investment (FDI) within G20 countries and analyzed their combined impact on GDP growth. It aimed to explore immediate and long-term relationships to inform sustainable growth strategies. Design/Methodology/Approach : The analysis employed the autoregressive distributed lag (ARDL) methodology, complemented by Johansen cointegration tests, vector error correction model (VECM), and Granger causality tests for robustness. Time-series data from the World Development Indicators (WDI) were used to assess the effects of trade openness on FDI inflows and GDP growth across G20 nations. The study considered data from 1990 – 2019. Findings : The findings indicated that trade openness maintained a long-run equilibrium relationship with GDP, highlighting that liberal trade policies contributed positively to FDI and economic performance. However, the short-run dynamics were marked by instability due to geopolitical uncertainties, exchange rate fluctuations, and institutional weaknesses. The results also revealed immediate causal linkages between trade openness and GDP. Practical Implications : The results suggested that G20 policymakers should prioritize reducing non-tariff barriers and improving regulatory transparency to attract FDI and sustain growth. The ARDL-based insights provided concrete guidance for shaping effective trade and investment strategies. Originality/Value : This research used advanced panel econometric techniques to offer empirical evidence of time-dependent, reciprocal relationships between trade openness, FDI, and GDP growth. It contributed to the trade-growth literature by clarifying how trade liberalization could drive growth via investment channels and institutional reform.